2020
DOI: 10.1186/s12984-020-00706-1
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological signatures of hand motor response to dual-transcranial direct current stimulation in subacute stroke: a TMS and MEG study

Abstract: Background: Dual transcranial direct current stimulation (tDCS) to the bilateral primary motor cortices (M1s) has potential benefits in chronic stroke, but its effects in subacute stroke, when behavioural effects might be expected to be greater, have been relatively unexplored. Here, we examined the neurophysiological effects and the factors influencing responsiveness of dual-tDCS in subacute stroke survivors. Methods: We conducted a randomized sham-controlled crossover study in 18 survivors with first-ever, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 68 publications
(86 reference statements)
0
24
0
Order By: Relevance
“…Stagg et al, showed cathodal tDCS improved UE motor performance with increased activity in ipsilesional M1 as compared with sham tDCS [ 36 ]. Recently, Kuo et al showed bilateral tDCS immediately increased cortical excitability and decreased transcallosal inhibition in ipsilesional M1, with a decrease in excitability and an increase in transcallosal inhibition in contralesional M1 [ 37 ]. Our results of cathodal and bilateral tDCS on corticomotor activity in contralesional M1 were in line with Kuo et al’s study.…”
Section: Discussionmentioning
confidence: 99%
“…Stagg et al, showed cathodal tDCS improved UE motor performance with increased activity in ipsilesional M1 as compared with sham tDCS [ 36 ]. Recently, Kuo et al showed bilateral tDCS immediately increased cortical excitability and decreased transcallosal inhibition in ipsilesional M1, with a decrease in excitability and an increase in transcallosal inhibition in contralesional M1 [ 37 ]. Our results of cathodal and bilateral tDCS on corticomotor activity in contralesional M1 were in line with Kuo et al’s study.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, different assessment domains may be combined in one statistical model. A recent example originates from the study by Kuo and colleagues of subacute stroke patients (N=18) [50]. The authors assessed a set of clinical, TMS-based and magnetoencephalography-based metrics.…”
Section: Combined Approachesmentioning
confidence: 99%
“… 9 , 15 Accordingly, the more reliable parameter to evaluate the amount of structural reserve is the presence or absence of MEP, the former being associated with more structural reserve and the latter linked to less reserve. 9 , 16 On the other hand, it has been demonstrated that tDCS can produce prolonged changes in motor cortical excitability both in healthy subjects 17 and in stroke patients, 18 resulting in MEP suppression when tDCS is delivered with cathodal montage and MEP increase when delivered with anodal montage. 19 , 20 Accordingly, tDCS has the potentiality of amending inter-hemispheric imbalance in sub-acute stroke.…”
Section: Introductionmentioning
confidence: 99%